The Isthmus of Corinth : Crossroads of the Mediterranean World - Pettegrew, David K. (Book collections on Project MUSE., 2016)
"The narrow neck of Corinthian territory that joins the Peloponnese with the Greek mainland was central to the fortunes of the city of Corinth and the history of Greece in the Roman era. This situated Corinth well for monitoring land traffic both north and south, as between Athens and Sparta, and also sideways across the Isthmus, between the Gulf of Corinth to the west and the Aegean Sea to the east. David Pettegrew's new book investigates the Isthmus of Corinth from the Romans' initial presence in Greece during the Hellenistic era to the epic transformations of the Empire in late antiquity. A new interpretation of the extensive literary evidence outlines how the isthmus became the most famous land bridge of the ancient world, central to maritime interests of Corinth, and a medium for Rome's conquest, annexation, and administration in the Greek east. A fresh synthesis of archaeological evidence and the results of a recent intensive survey on the Isthmus describe the physical development of fortifications, settlements, harbors, roads, and sanctuaries in the region. The author includes chapters on the classical background of the concept isthmos, the sacking of Corinth and the defeat of the Achaean League, colonization in the Late Roman Republic, the Emperor Nero's canal project and its failure, and the shifting growth of the Roman settlement in the territory"--Publisher's website.